2020
DOI: 10.5530/jyp.2020.12s.41
|View full text |Cite
|
Sign up to set email alerts
|

Design and Characterization of Bilayered Floating Tablets of Clopidogrel Bisulfate and Aspirin using Natural Gums

Abstract: Objectives: In present investigation, an attempt was made to develop bilayered floating tablets of clopidogrel bisulfate and aspirin using natural gums as release retarded material. Clopidogrel bisulfate and aspirin are anti-platelet agents. Methodology: Clopidogrel bisulfate is a suitable candidate for formulating as gastro retentive dosage form as it has absorption window in stomach and solubility in the acidic pH. Sodium bicarbonate and citric acid were used to get desired floating properties. The effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…In clopidogrel bisulphate (pure), a strong absorbance band was found at 1750.732 cm –1 due to C = O stretching vibrations, at 1171.732 due to C-O stretching and at 2986–2830 cm –1 due to O–H stretching of the hydrogen sulfate moiety. This study aligns well with the values published in the literature [ 37 , 38 , 42 ]. In case of aspirin, carboxylic acid is the principal functional group.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In clopidogrel bisulphate (pure), a strong absorbance band was found at 1750.732 cm –1 due to C = O stretching vibrations, at 1171.732 due to C-O stretching and at 2986–2830 cm –1 due to O–H stretching of the hydrogen sulfate moiety. This study aligns well with the values published in the literature [ 37 , 38 , 42 ]. In case of aspirin, carboxylic acid is the principal functional group.…”
Section: Resultssupporting
confidence: 93%
“…The IR spectra suggested that there were no significant changes in the peaks, thus, it is concluded that the excipients used in the formulations are very much compatible with both the drugs. This study provides a good understanding of the existing literature [ 40 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation